PERANCANGAN PENGURANGAN JUMLAH DEFECT PADA KENDARAAN PADA PROSES PENGIRIMAN DI VDC DAN VDC TO VDC MENGGUNAKAN METODOLOGI SIX SIGMA DI PT TOYOTA ASTRA MOTOR - Sarah, Zaneta
PT Toyota Astra Motor or abbreviated as TAM is a company that distributes, imports, and sells Toyota vehicle in Indonesia. Division in TAM that is responsible for Toyota vehicles logistics management is Vehicle Logistics Division. One of the problems that the company experienced is the number of defects that occur on vehicles during the delivery process. The company establishes a defect allowance of 1,5% while the average number of defects in 2019 is 3,13%. Therefore, this research intends to design reduction in the number of defects that occur during the vehicle delivery process. The methodology used in this research is six sigma with define, measure, analyze, improve, control (DMAIC) approach. At the define phase, the problem was defined specifically the research object was determined, problem was formulated, and type of defects were observed. From this define phase, it is formulated to reduce the number of defects during VDC (Vehicle Distribution Center or in yard) process and VDC to VDC process. At the measure phase, process stability was measured using p attribute control chart and process capability measurement was carried out using the calculation of sigma values. From this phase, it was found that the processes were stable with 0,00306 and 0,00417 average defect fraction along with sigma value of 3,55 and 3,47 for VDC (in yard) and VDC to VDC process. Next at the analyze phase, problem mapping and root causes identification were carried out. In problem mapping, problem breakdown was done using Pareto chart to determine research focus include types of defects that will be researched furtherly while root causes of defects were identified using 5 Whys and cause-and-effect diagram also priority determination using FMEA (failure mode and effect analysis) with the result of total eight subfactors. Then at the improve phase, alternative solutions were designed and twelve alternative solutions were obtained namely design alternative method of animals handling to reduce animal drops, design user guidance work method to do fallout monitoring, design work procedure for car cover maintenance, remove car cover (delivery process without using car cover), establish monitoring car cover usage database, conduct an internal training for drivers, conduct an internal campaign for drivers, use car carrier with roof, prune trees, use side cover on the car carrier, and sheathe inside of the car carrier, also design vehicle location arrangement. Furthermore, project management was carried out to design the implementation of alternative solutions that is arranging an alternative solutions implementation timeline.